Nivel de Seguridad del Paciente que Brinda la Enfermera en el Centro Quirúgico-Hospital Victor Lazarte Echegaray - García Cordova, Nelly (2019)
The present research study of quantitative type prospective descriptive method cross-sectional, was performed in the service of the surgical center of the Hospital Víctor Lazarte Echegaray during the months of September and November 2016, with the objective of determining the level of patient safety that provides the nurse. The population consisted of 23 nurses who met the established inclusion criteria. The information was obtained through the instrument: Questionnaire "Level of patient safety provided by the nurse focused on four dimensions: Emotional, physical, risk management and environmental conditions.The results conclude that there is an average level of surgical patient safety.